2021
DOI: 10.3389/fgene.2021.620337
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Dropout Is a Common Phenomenon That Reduces the Diagnostic Yield of PCR-Based Sequencing of Targeted Gene Panels

Abstract: Primary cardiomyopathies (CMPs) are monogenic but multi-allelic disorders with dozens of genes involved in pathogenesis. The implementation of next-generation sequencing (NGS) approaches has resulted in more time- and cost-efficient DNA diagnostics of cardiomyopathies. However, the diagnostic yield of genetic testing for each subtype of CMP fails to exceed 60%. The aim of this study was to demonstrate that allelic dropout (ADO) is a common phenomenon that reduces the diagnostic yield in primary cardiomyopathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…Moreover, this whole-exome study demonstrated the overrepresentation of several disease-causing variants for Mendelian disorders, such as phenylketonuria (PAH, rs5030858), Wilson's disease (ATP7B, rs76151636), factor VII deficiency (F7, rs36209567), and the kyphoscoliosis type of Ehlers-Danlos syndrome (FKBP14, rs542489955). For the Russian population, however, pathogenic variant frequencies were reported mostly for relatively small cohorts including patients and their families and targeted at specific genes and disorders, for example, familial hypercholesterolemia (Meshkov et al, 2021;Miroshnikova et al, 2021); cystic fibrosis, phenylketonuria, alpha-1 antitrypsin deficiency, and sensorineural hearing loss (Kiseleva et al, 2020;Petrova et al, 2020); cardiomyopathy (Marakhonov et al, 2019;Zaklyazminskaya et al, 2019;Kulikova et al, 2021;Shestak et al, 2021); and breast and ovarian cancer (Brovkina et al, 2018;Solodskikh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this whole-exome study demonstrated the overrepresentation of several disease-causing variants for Mendelian disorders, such as phenylketonuria (PAH, rs5030858), Wilson's disease (ATP7B, rs76151636), factor VII deficiency (F7, rs36209567), and the kyphoscoliosis type of Ehlers-Danlos syndrome (FKBP14, rs542489955). For the Russian population, however, pathogenic variant frequencies were reported mostly for relatively small cohorts including patients and their families and targeted at specific genes and disorders, for example, familial hypercholesterolemia (Meshkov et al, 2021;Miroshnikova et al, 2021); cystic fibrosis, phenylketonuria, alpha-1 antitrypsin deficiency, and sensorineural hearing loss (Kiseleva et al, 2020;Petrova et al, 2020); cardiomyopathy (Marakhonov et al, 2019;Zaklyazminskaya et al, 2019;Kulikova et al, 2021;Shestak et al, 2021); and breast and ovarian cancer (Brovkina et al, 2018;Solodskikh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Machine-learning methods can also improve significantly recognition of the regulatory sequence patterns, splice sites placed in deep intronic areas, functional annotation of the genes, and co-functional relationship of the gene products. Complementary to the data interpretation, AI-based algorithms might better elicit technical artifacts and other phenomena, such as allelic drop-out, that reduce diagnostic yield of genetic testing ( Shestak et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ADO is a common phenomenon that reduces the efficiency of PCR-based targeted sequencing. It was first described as a "partial amplification failure" causing a potential source of misdiagnosis for both dominant and recessive diseases [12]. The ADO phenomenon involves selective allele amplification during the PCR process.…”
Section: Discussionmentioning
confidence: 99%